Hydatid Disease of The Brain Parenchyma: A Systematic Review - Fattah H. Fattah; Azad Star Hattam; Zana Omar kak Abdullah; Khanda A. Anwar; Rezhen J. Rashid; Abdullah K. Ghafour; Alaa B. Latif; Hiwa O. Abdullah; Sasan M. Ahmed; Abdullah Dler Ahmad (Barw Medical Journal, 2025)
Abstarct Introduction Isolated brain hydatid disease (BHD) is an extremely rare form of echinococcosis. A prompt and timely diagnosis is a crucial step in disease management. This study is a systematic review of studies on intra-parenchymal BHD. Methods Studies that had the following properties were included: 1) The intra-parenchymal brain infection had been confirmed by diagnostic modalities, surgical findings, or histopathology. 2) The patient details were provided in the study. 3) The cystic lesion [s] were located intracranially. Results Altogether, 112 studies with a sample size of 178 cases met the inclusion criteria. Males (60.1%) showed a higher prevalence of the disease than females (38.2%). Most of the cases (64%) were affected during the first and second decades of their lives. Left-side multi-lobe involvement was the most common type of involvement (28.1%), followed by right-side multi-lobe involvement (26.4%). Surgery was the primary treatment option (97.2%), with the Dowling technique or the modified Arana-Iniguez method as the preferred approach. The total recurrence and mortality rates were 7.3% and 3.4%, respectively. Conclusion The definitive treatment for BHD is surgery, with the aim of removing cysts intact or excising mass lesions completely. A history of cyst rupture during operation may increase the likelihood of recurrence, and an extensive follow-up is required. Introduction Hydatid disease (HD) is a parasitic infection caused by the larvae of the tapeworm Echinococcus. Different genera of this microorganism can cause disease; however, in humans, two species have major clinical sequelae. Echinococcus granulosus results in cystic disease, the most common type, while Echinococcus multilocularis causes alveolar echinococcosis (AE), presenting as a mass or cystic lesion. The latter form of the disease is more invasive and aggressive, accompanied by numerous diagnostic and management challenges [1-3]. The most common organs affected by hydatidosis are the liver and lungs. However, other parts of the body can also be affected, including the bones, pericardium, orbits, ovaries, central nervous system (CNS), and other organs. In the literature, 2–3% of cases show involvement of the CNS. The incidence of isolated brain involvement is reported to be 1–2% of all cases of echinococcosis, representing approximately 2% of all intracranial space-occupying lesions [4-6]. Brain hydatid disease (BHD) is endemic in many regions where livestock raising is prevalent, and human-animal contact is common. The incidence varies geographically, with higher rates reported in rural areas. However, globalization and increased travel have led to sporadic cases being reported in non-endemic regions as well. Humans can become infected through the ingestion of parasite eggs in contaminated food, water, or by direct contact with infected dogs, canines, and sheep [7,8]. Most cases of intracerebral echinococcosis are diagnosed in pediatrics (50-75%) [9]. The clinical presentation of hydatidosis depends on the patient's age, the size, number, and location of the cyst, as well as the host's immune system. Patients with HD can remain asymptomatic for long periods, as the lesions take years to develop. When they grow well, intracranial hypertension secondary to the mass effect on the surrounding tissues is usually the first clinical sign of brain involvement. The disease may not cause focal neurological signs until they become enlarged [10-12]. In the literature, several reviews have been published on cerebral HD; however, there is a scarcity of systematic reviews on the topic. This study is a systematic review of studies on intra-parenchymal BHD published over the last two decades [1-112]. Methods Study design and reporting standards The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Search strategy A systematic review of all published studies on brain parenchymal HD was conducted from 2000 to 2024 using the following databases: Google Scholar, PubMed/MEDLINE, Cochrane Library, Science Direct, and EMBASE. The keywords used in the search included: [brain OR intraparenchymal OR cerebral OR intracerebral OR cerebrum] AND [hydatid OR hydatidosis OR echinococcoses OR echinococcosis OR echinococcal OR echinococcus]. Eligibility criteria Non-English language studies and those unrelated to humans were excluded before or during the initial screening. Studies of BHD were included if: 1) Diagnostic modalities, surgical findings, or histopathology confirmed the intraparenchymal brain infection. 2) Patient details were provided in the study. 3) Studies published in predatory journals (inappropriately peer-reviewed) and those not meeting inclusion criteria were excluded [113]. Study selection Titles and abstracts of identified studies were initially screened, followed by full-text screening to assess eligibility. Data extraction Data extracted from eligible studies included study design, country of study, patient age, gender, residency, symptoms, medical history of HD, cyst characteristics, diagnosis, management, follow-up, and outcomes. Data analysis Data were analyzed qualitatively (descriptive analysis) using the Statistical Package for the Social Sciences (SPSS) version 27.0 software Results In total, 318 studies were obtained from the resources. Before any screening, 38 of them were directly excluded due to duplication, non-English language, non-articles, and animal studies. Following the initial screening, 92 studies did not meet the inclusion criteria and were excluded. The remaining 188 studies underwent full-text screening, and 122 of them were assessed for eligibility. Ultimately, 112 studies (comprising 178 cases) met the inclusion criteria (Figure 1). The characteristics of the included studies are shown in Table 1. Out of these studies, 101 (90.2%) were case reports, 10 (8.9%) were case series, and one (0.9%) was a retrospective cohort study. Most of the cases were reported in Turkey (24.1%), followed by Iran (16.7%), India (15.2%), and Morocco (9.8%). Males (60.1%) showed a higher prevalence of the disease than females (38.2%). Most of the cases (64%) occurred in the first and second decades of life, with a mean age of 20.44 ± 16.76 years. There were 71 cases (39. 9%) in rural areas and eight cases (4.5%) in urban areas. The residency of the remaining 99 cases (55.6%) was not reported. The type of the disease was cystic in 158 cases (88.8%) and alveolar in 20 cases (11.2%). Thirteen (7.3%) cases had a previous history of HD. The most commonly presented symptoms were signs of raised intracranial pressure, including headache (62.9%), vomiting (43.3%), followed by seizure (30.3%) and paresis (28.7%). Multiple organ involvement was present in 48 (27%) cases, involving the lung, liver, kidney, adrenal gland, blood vessels, or bones. The disease was primary with a single cyst or lesion in 118 patients (66.3%), primary with multiple cysts in 27 (15.1%), secondary with a single cyst in 23 (13%), and secondary with multiple cysts in 10 (5.6%). Left-side multi-lobe involvement was the most common type of involvement (28.1%), followed by right-side multi-lobe involvement (926.4%) and parietal lobe involvement (18.5%). Serology had been done in 55 cases (30.9%), and it was positive in 34 (19.1%). Computed tomography scans (CT) or magnetic resonance imaging (MRI) were used in all cases. Surgery was the main treatment option (97.2%). The Dowling technique, or modified Arana-Iniguez, was the method of choice (95.5%). Surgery in three cases (1.7%) was done through the Burr-hole technique instead of open craniotomy. Conservative management was performed in five cases (2.8%). The patients underwent follow-up with a mean interval of one year. Recurrence was reported in 13 cases (7.3%). Among those, six cases (46.1 %) had intra-operative complications of traumatic rupture of the cyst, and two cases (15.4 %) had a surgical puncture of the cyst. The remaining five cases (38.5%) did not experience any intraoperative complications. The mortality rate was 3.4% (Table 2). Table 1. Raw data of the included studies. Author Country Study design No Age Sex Presenting symptoms Imaging ISHC No. of cyst [s] in brain Location of cyst [s] in brain Size [cm] Serology Type of management Pre-Op complication Intra-Op complication Post-Op complication Adjuvant therapy Follow up* outcome Svrckova et al [1] United Kingdom Case report 3 30 M Headache, seizure MRI Yes >1 Right parietal, right temporal N/A Positive Conservative [Albendazole/praziquantel/steroid/antiepileptic] N/A N/A N/A None Improved 26 M Collapse, slurred speech, seizure, left side hemiparesis CT, MRI Yes 1 Right parietal and basal ganglia N/A Positive Conservative [Albendazole/Praziquantel/steroid/Antiepileptic] N/A N/A N/A None Improved 37 M Dry cough MRI Yes >1 Bilateral hemisphere N/A Positive Conservative [Albendazole] N/A N/A N/A None Improved Altibi et al [2] Brazil Case report 1 13 M Headache, nausea CT, MRI Yes 1 Right parieto-occipital 4.7 Negative Surgical removal [Dowling]/neuronavigation None None None N/A N/A Casulli et al [3] Italy Case report 1 6 M Right side hemiparesis CT, MRI Yes 1 Left fronto-parietal 6.8 Negative Surgical removal/neuronavigation None None Seizure, headache, worsened right hemiparesis, peri-lesional edema Albendazole, Antiepileptic,Steroid Improved Lakhdar et al [4] Morocco Case report 1 30 M Headache, right side hemiparesis MRI Yes >1 Left fronto-parietal N/A Negative Surgical removal None Rupture of cysts None Albendazole, Antibiotics, Antiepileptic Recovered Fariba Bi. [5] Iran Case report 1 18 F Headache, nausea, vomiting MRI Yes 1 Right temporal N/A N/A Surgical removal None None None Albendazole, anticonvulsant Recovered Saleh et al [6] Egypt Case series 4 9 M Drowsiness, vomiting, blurred vision, headache CT, MRI Yes >1 Right parieto-occipital N/A N/A Surgical removal [Dowling] None None None Albendazole N/A 10 M Seizure CT, MRI Yes 1 Right frontal N/A N/A Surgical removal [Dowling] None None None Albendazole N/A 12 M Seizure CT, MRI Yes 1 Left fronto-parietal N/A N/A Surgical removal [Dowling] None None None Albendazole N/A 14 F Headache CT, MRI Yes 1 Right parieto-occipital N/A N/A Surgical removal [Dowling] None None None Albendazole N/A Alomari et al [7] Saudi Arabia Case report 1 8 F Bilateral exophthalmos, blurred vision, headache CT Yes 1 Left frontal 15.3 Negative Surgical removal [Dowling] None None Seizure Albendazole Recovered Hafedh et al [8] Iraq Case report 1 27 M Seizure, headache, left side hemiparesis CT, MRI Yes 1 Right hemisphere N/A N/A Surgical removal [Dowling] None None None Albendazole Improved Umut et al [9] Turkey Case report 1 14 M Double vision, headache nausea, vomiting MRI Yes 2 Left occipital lobe, right insula 1st: 5.6 2nd:2.6 Negative Surgical removal [Dowling] first occipital cysts and after 6 m temporal insula None None None Albendazole Recovered Çavusoglu et al [10] India Case report 1 8 F Left side hemiparesis, left side mouth deviation, slurred speech CT, Contrast MRI Yes 1 Left fronto-parietal 10.2 N/A Surgical removal [Dowling] None None None Albendazole N/A Garg et al [11] India Case report 1 8 F Left side hemiparesis, left side mouth deviation, slurred speech CT, Contrast MRI Yes 1 Left fronto-parietal 10.2 N/A Surgical removal [Dowling] None None None Albendazole N/A Raouzi et al [12] Morocco Case series 4 14 M Seizure CT, MRI Yes 1 Right parietal area N/A Negative Surgical removal [Dowling] None None None Albendazole N/A 4 M Headache, vomiting CT, MRI Yes 1 Right fronto-parietal 7.05 Positive Surgical removal [Dowling] None None None Albendazole N/A 3 M Seizure CT, MRI Yes 1 Right parietal lobe N/A Positive Surgical removal [Dowling] None None None Albendazole N/A 22 F Seizure CT, MRI Yes >1 Left fronto-parietal N/A Negative Surgical removal [Dowling] None None None Albendazole N/A Assefa et al. [13] Ethiopia Case series 4 8 M Hemiparesis, nausea and vomiting Contrast CT Yes 1 Left fronto-parietal + daughter cyst N/A N/A Surgical Removal None Rupture of Cyst Cystic abscess, peri-cystic vasogenic edema N/A Recurrence 5 F Hemiparesis, nausea and vomiting Contrast CT Yes 1 Right fronto-parietal N/A N/A Surgical Removal None None None N/A N/A 10 F Hemiparesis, nausea and vomiting Contrast MRI Yes 1 Right parietal N/A N/A Surgical Removal None None None N/A N/A 29 M Hemiparesis, nausea and vomiting Contrast MRI Yes 1 Right parietal N/A N/A Surgical Removal None None None N/A N/A Tanki et al [14] India Case series 9 10 M Seizure CT, MRI Yes 1 Right frontal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 12 F Headache, nausea, vomiting, hemiparesis CT, MRI Yes >1 Left parietal N/A N/A Surgical removal [Dowling] None Rupture of Cyst N/A Albendazole Recurrence 12 M Seizure, headache, nausea, vomiting CT, MRI Yes 1 Right parietal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 10 M Headache, nausea, vomiting CT, MRI Yes 1 Left parieto-occipital N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 11 M Seizure, hemiparesis CT, MRI Yes 1 Right parietal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 16 F Seizure CT, MRI Yes 1 Left frontal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 14 M Seizure, hemiparesis CT, MRI Yes >1 Right parietal N/A N/A Surgical removal [Dowling] None Rupture of Cyst N/A Albendazole Recurrence 7 F Seizure CT, MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered 12 F Seizure, hemiparesis CT, MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None None N/A Albendazole Recovered Noori et al [15] Iraq Case report 1 26 M Headache, nausea, vomiting CT Yes 1 Right temporo-parietal N/A N/A Surgical removal [Dowling] None None None N/A N/A Haradhan et al [16] Bangladesh Case report 1 14 M Headache Contrast CT, Contrast MRI Yes 1 Right fronto-parietal 12.48 N/A Surgical removal None None Right frontoparietal subdural hygroma, hydrocephalus, pseudocyst Albendazole N/A Panda et al [17] India Case report 1 4 M Seizure CT, MRI Yes 1 Left fronto-parietal 4.47 N/A Surgical removal [Dowling] None Rupture of Cyst None N/A N/A Sharifi et al [18] Iran Case report 1 44 M Mood swings, restlessness, and headache CT Yes 1 Right frontoparietal lobe N/A N/A Surgical removal None None None Albendazole N/A Aydin et al [19] Turkey Case series 2 9 F Headache, vomiting, bilateral decreased vision, left side tremor, left side hemiparesis CT, MRI Yes 1 Right fronto-temporo-parietal 9.81 Negative Surgical removal [cavity placed balloon/ Dowling] None None None N/A N/A 18 M Headache, vomiting, blurred vision, fever, quadriparesis CT, MRI Yes 1 Right fronto-temporo-parietal 8.96 Negative Surgical removal [cavity placed balloon/ Dowling-Orlando] None None None N/A Recovered Çakir et al [20] Turkey Case report 1 6 M Headache MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None Cardiac arrest/death N/A N/A Death Ponnambath et al [21] India Case report 1 40 M Headache, seizure Contrast MRI No 1 Left occipital lobe 3 N/A Surgical removal/neuronavigation None None None Albendazole Minimal visual field defect İzgi et al [22] Turkey Case report 1 5 M Headache, nausea, vomiting, deviation of the eyes MRI Yes 1 Right parietal lobe 6.92 N/A Surgical removal [Dowling] None None None N/A N/A El Ouarradi et al [23] Morocco Case report 1 11 M Nausea, vomiting CT Yes 1 Right fronto-parieto-temporal lobe 9.75 Positive Surgical removal [Dowling] None Shock/cardiac arrest/death N/A N/A Death Baboli et al [24] Iran Case report 1 19 M Headache, left hemiparesis Contrast MRI Yes 1 Right fronto-parietal lobe 8 Positive Surgical removal [Dowling] None None None Albendazole Improved Arega et al [25] Ethiopia Case report 1 8 F Headache, vomiting Contrast MRI Yes 1 Right temporal 13.27 N/A Surgical removal None None None Albendazole Recovered Altaş et al [26] Turkey Case report 1 26 F Headache, nausea, vomiting Contrast CT, MRI Yes 1 Right parieto-occipital 7.95 Positive Surgical removal [Dowling] None None None Albendazole N/A Madeo et al [27] USA Case report 1 82 F Emergency case CT, MRI Yes 1 Left hemisphere 4.08 Positive Conservative [Albendazole] N/A N/A N/A None Stable cyst Menschaert et al [28] Morocco Case report 1 5 F Seizures MRI Yes 1 Left parietal N/A Positive Surgical removal None Puncture of Cyst None Albendazole Learning disabilities Şule et al [29] Turkey Case report 1 83 M Headache, forgetfulness Contrast MRI No 1 Right frontal lobe 4 N/A Surgical removal None None None N/A N/A Benhayoune et al [30] Morocco Case report 1 18 F Headache, vomiting, seizure Contrast MRI No 1 Right parieto-occipital 7.9 N/A Surgical removal [Arana] None None None Albendazole, Antiepileptic Recovered Vikaset al [31] India Case report 1 20 M Seizure, right side paresthesia, headache, vomiting Contrast CT, contrast MRI Yes >1 Left fronto-parietal N/A N/A Surgical removal None None None Albendazole Recovered Reddy et al [32] India Case report 1 35 F Headache, vomiting, altered sensorium, loss of consciousness Contrast CT Yes 5 Both parietal lobes N/A N/A Surgical removal None None None N/A Recovered Al-Rawi et al [33] Iraq Case series 8 3.5 F N/A CT Yes 1 Left parietal N/A N/A Surgical removal None None None Antiepileptic Recovered 7 F N/A CT Yes 1 Right parietal N/A N/A Surgical removal None Rupture of Cyst Delayed recovery Antiepileptic Recurrence 11 M N/A CT Yes 1 Left fronto-parietal N/A N/A Surgical removal None None None Antiepileptic Recovered 13 F N/A CT Yes 1 Right frontal lobe N/A N/A Surgical removal None None None Antiepileptic Recovered 15 M N/A CT Yes 1 Left fronto-parietal N/A N/A Surgical removal None None None Antiepileptic Recovered 15 M N/A CT Yes 1 Right fronto-parietal N/A N/A Surgical removal None None None Antiepileptic Recovered 35 M N/A CT Yes 1 Left fronto-parietal N/A N/A Surgical removal None None None Antiepileptic Recovered 14 F N/A CT Yes 1 Left frontal N/A N/A Surgical removal None None None Antiepileptic Recovered Naderzadeh et al [34] Iran Case report 1 12 M Headache, nausea, vomiting, fever, decreased vision MRI Yes 1 Left parieto-occipital 4.56 N/A Surgical removal None None Visual deficit Albendazole Myopia, occasional seizure Shafiei et al [35] Iran Case series 3 3 M Headache CT Yes 1 Left temporo-parietal 5.83 N/A Surgical removal None None None Albendazole, Antiepileptic Recovered 59 F Headache, fever CT Yes 1 Right parieto-occipital 8.48 N/A Surgical removal None None None Albendazole, Antiepileptic Recovered 53 F Angiopathy, nausea, vomiting CT Yes 1 Left fronto-occipital N/A N/A Surgical removal None Rupture of Cyst None Albendazole, Antiepileptic Recurrence Nechi et al [36] Tunisia Case report 1 50 F Seizure CT, MRI Yes 1 Right frontal lobe 4.97 N/A Surgical removal None None None Albendazole Recovered Ekici et al [37] Turkey Case report 1 12 M Headache, vomiting, diplopia CT Yes >1 Right parieto-occipital N/A Negative Surgical removal [Dowling]/neuronavigation None None None Albendazole Recovered Bagheri et al [38] Iran Case report 1 18 M Nausea,vomiting, right side hemiparesis CT, MRI Yes 1 Left temporal 6 N/A Surgical removal [Dowling] None None None Albendazole Recovered Bušić et al [39] Croatia Case report 1 37 F Headache, vomiting, balance difficulties, left side hemiparesis CT, MRI Yes 5 Right parietal lobe N/A Positive Surgical removal None None Wound infection and osteomyelitis Albendazole Recurrence Nashibi et al. [40] Iran Case report 1 59 M Disorientation, right side hemiparesis, headache, dysarthria CT, MRI Yes 1 Left parieto-temporal N/A N/A Surgical removal [Dowling] None None None N/A Improved Ammor et al [41] Morrocco Case report 1 4 N/A Weakness, headache, vomiting Contrast MRI Yes 1 Right fronto-temporo-parietal N/A N/A Surgical removal None None None N/A Headache, subdural hygroma Alok et al [42] Syria Case report 1 5 F Right side hemiparesis CT, MRI Yes 1 Pons 2.1 Positive Surgical removal [Dowling-Orlando] None None None Albendazole Improved Chatzidakis et al [43] Greece Case report 1 27 M Quadriparesis, headache, nausea, vomiting CT, MRI Yes >1 Bilateral frontal, bilateral occipital, cerebellum N/A N/A Surgical removal [3 times] None None Generalized seizure post 1st OP Albendazole Recovered Panagopoulos et al [44] Greece Case report 1 11 M Headache, vomiting Contrast CT, contrast MRI Yes 1 Right fronto-parietal 6.85 Negative Surgical removal/neuronavigation None None None Albendazole Improved Karaaslan et al [45] Turkey Case report 1 22 M Nausea,vomiting, headache CT,MRI Yes 1 Left parieto-occipital 6.92 N/A Surgical removal [Dowling] None None None Albendazole Recovered Hajhouji et al [46] Morocco Case report 1 17 F Seizure Contrast MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Recovered Tascu et al [47] Romania Case report 1 3 N/A Post cranio-cerebral trauma Contrast CT, MRI Yes 1 Left fronto-parieto-occipital lobe 10 N/A Surgical removal [Arana] None None None N/A Subdural hematoma Ghaemi et al [48] Iran Case report 1 28 M Headache, nausea, vomiting CT,MRI No 1 Right temporal 6 N/A Surgical removal None None None N/A N/A Ganjeifar et al [49] Iran Case report 1 13 M Fever ,abdominal pain CT, MRI Yes 1 Left parieto-occipital N/A Positive Surgical removal [Dowling] None None None Albendazole Recovered Nemati et al [50] Iran Case report 1 6 M Ataxia, left side hemiparesis CT,MRI Yes 1 Right fronto-parietal 13.29 Negative Surgical removal [Dowling] None None None Albendazole Improved Mehrizi et al. [51] Iran Case report 1 5 F Headache, nausea, vomiting CT Yes 1 Fronto-parietal 10 N/A Surgical removal [Dowling] None None None Albendazole Recovered Fakhouri et al [52] Syria Case report 1 5 F Headache, vomiting, difficult walking CT, MRI Yes 1 Right Cerebellum 6 N/A Surgical removal [Dowling] None None None Albendazole Recovered Ghasemi et al [53] Iran Case report 1 8 F Malaise, vomiting, headache CT, contrast MRI Yes 1 Left temporo-parieto-occipital N/A Negative Surgical removal [Dowling] None None None Albendazole Recovered Mallik et al. [54] India Case report 2 10 M Headache, vomiting, right side hemiparesis, aphasia MRI Yes 1 Left temporo-parietal 10.32 N/A Surgical removal [Dowling] None Rupture of Cyst None Albendazole, Antibiotics, Antiepileptic, Steroids Improved 16 M Decreased vision, headache, vomiting CECT Yes 1 Left fronto-temporo-parietal N/A Positive Surgical removal [Dowling] None Rupture of Cyst None Albendazole Seizure, unconsciousness Arora et al[55] India Case report 1 9 F Seizure, decreased vision, headache, vomiting CT Yes 1 Left parietal lobe 7.23 Positive Surgical removal [Dowling] None None None N/A N/A Al-Musawi et al [56] Iraq Case report 1 14 F Seizure CT Yes 1 Left parietal N/A N/A Burr-hole surgical removal Deterioration in the consciousness, right side hemiparesis, apnea None None Albendazole, anticonvulsant Recovered Ghasem et ali [57] Iran Case report 1 30 F Seizure, headache, intellectual impairment, abnormal behavior CT, MRI Yes 1 Left frontal N/A N/A Surgical removal [Dowling] None None None N/A Recovered Polat et al. [58] Turkey Case report 1 45 M Personality disorder, nausea, vomiting CT, MRI Yes 1 Left fronto-parietal N/A Positive Surgical removal [Dowling] None None None Albendazole Recurrence & Death Hmada et al [59] Morocco Case report 2 5 F Decreased vision, tremor CT Yes 1 Right fronto-temporo-parietal N/A N/A Surgical removal [Arana] None None None Albendazole, Antiepileptic Improved 5 F Right side heaviness N/A Yes 1 Right fronto-temporo-parietal N/A N/A Surgical removal [Arana] None None None Albendazole, anticonvulsant Recovered Senapati, et al [60] India Case report 2 22 M Vomiting, disorientation CT, MRI Yes >1 Left parieto-occipital N/A N/A Surgical removal [Dowling] None Cyst wall puncture None N/A Recovered 40 M Seizure, headache, vomiting, right side hemiparesis CT Yes 1 Left fronto-parietal N/A N/A Surgical removal [Dowling] None None None N/A Recovered Imperato et al [61] Italy Case report 1 9 M Headache, diplopia CT, MRI Yes 1 Right temporo-parieto-occipital N/A N/A Surgical removal [Dowling] None None None Albendazole Recovered Ramosaço et al [62] Albania Case report 1 22 F Headache, vomiting, seizure MRI Yes 6 Left frontal lobe, left frontal-parietal, left temporo-parietal, right occipital and right frontal 1st:2.79 2nd:4.18 3rd:4.29 4th:2.89 5th:4.09 6th:2.84 Positive Surgical removal None None None Albendazole, Antiepileptic Encephalomalacia Ravanbakhsh et al [63] Iran Case report 1 12 M Vision disturbance MRI Yes 1 Left parietal 8 N/A Surgical removal [Dowling] None None None Albendazole N/A Pulavarty [64] India Case report 1 16 F Generalized seizure CT Yes 1 Left fronto-temporal 4.89 N/A Surgical removal [Dowling] None Rupture of cyst None Albendazole Recovered Shastry et al. [65] Iran Case report 1 7 F Blurred vision CT Yes 1 Left parieto-temporal 5.65 N/A surgical removal [Dowling] None None None N/A N/A Chen et al [66] China Case report 1 28 F Seizure MRI Yes 1 Right frontal N/A Positive Conservative [Albendazole] N/A N/A N/A None Size of the cyst reduced Kaushik et al [67] India Case report 1 53 M Seizure exacerbation CT Yes >1 Right parieto-occipital N/A N/A Surgical removal None None None Albendazole N/A Wani, et al [68] India Case report 1 13 M Generalized seizure, vomiting Contrast CT Yes 1 Right occipital 8.48 N/A Surgical removal None None None N/A Recovered Armanfar et al [69] Iran Case report 1 46 F Headache, blurred vision CT, MRI Yes >1 Right parieto-occipital N/A N/A Surgical removal None Rupture of cyst None Albendazole Recovered Khan et al [70] Pakistan Case report 1 8 M Headache, fever, vomiting Contrast MRI Yes 19 Right frontal N/A N/A Surgical removal [Dowling] None None None Albendazole, Steroid, Antibiotic, Antiepileptic Recovered Charles et al [71] Congo Case report 1 32 N/A Seizure, vomiting Contrast CT Yes 2 Bilateral hemisphere, right temporo-parietal 1st:1.02 2nd:6.87 N/A Surgical removal [Arana] None None None Albendazole, Steroid Improved Garg et al. [72] India Case report 1 47 M Headache, vomiting MRI Yes 7 Both sides of cerebrum N/A Positive Surgical removal [Dowling] None None None Albendazole Disturbed verbal output Abuhajar et al [73] Libya Case report 1 50 M Headache, left side numbness, left toes paresthesia, vomiting Contrast CT, MRI Yes 3 Right temporo-parietal 1st: 3.5 2nd: 3.8 3rd: 4.0 N/A Surgical removal N/A N/A N/A N/A N/A Umerani et al. [74] Pakistan Case report 1 22 F Headache CT, MRI Yes 1 Right temporo-parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Recovered Touzani et al. [75] Morocco Case report 1 5 M Vomiting , weakness, seizure CT Yes 1 Left fronto-parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Improved Kibzai et al [76] Pakistan Case series 3 10 M Left side paresthesia, nausea CT, contrast MRI Yes 1 Right temporo-parietal N/A N/A Surgical removal [Dowling] None Puncture of Cyst None Albendazole, Antiepileptic Recurrence 40 M Vomiting, altered behavior CT, MRI Yes 1 Left parieto-occipital N/A N/A Surgical removal [Dowling] None Rupture of cyst None Albendazole Recovered 72 M Seizure, personality disorder CT, MRI Yes 32 Right frontal N/A N/A Surgical removal None None None Albendazole Improved Duransoy et al [77] Turkey Case report 1 13 M Headache, nausea, vomiting CT Yes 1 Right temporo-parietal 10 N/A Surgical removal [Arana] None None Left hemiparesis, subdural hygroma Albendazole Improved Qureshi et al [78] Pakistan Case report 1 11 M Seizure MRI Yes 1 Left posterior-parietal N/A N/A Surgical removal [Dowling] None None None N/A N/A Senol et al. [79] Turkey Case report 1 6 F Headache with photophobia and phonophobia MRI Yes 1 Right frontotemporal 10.5 Negative Surgical removal [Dowling] None None None Albendazole, Antiepileptic Recovered Kandemirli et al [80] Turkey Case report 1 6 M Nausea, vomiting CT Yes 1 Right frontal extended to lateral ventricle 7.95 N/A Surgical removal [Dowling] None None None Albendazole, Antiepileptic Recovered Bahannanet al [81] Yemen Case report 1 17 M Imbalance, ataxia, falls, right side hemiparesis, fever, headache, decreased visual acuity, diplopia. CT Yes 1 Right fronto-parietal 5 N/A Surgical removal None None None Albendazole Recovered Kumar et al [82] India Case report 1 25 M Headache, vomiting, right side weakness, seizure Contrast CT, MRI Yes 1 Left parietal N/A N/A Surgical removal None None None N/A N/A Agrawal et al [83] India Case report 1 25 M Difficulty walking, seizure CT, contrast MRI Yes 1 Left fronto-parietal 24.63 N/A Surgical removal None None None Albendazole N/A Mustafa et al [84] Iraq Case report 1 2 M Focal seizure CT Yes 1 Left parietal 6 N/A Surgical removal [Dowling] None None None none Recovered IJaz et al [85] Pakistan Case report 1 8 M Headache, fever, right-side hemiparesis, difficult walking CT Yes 1 Left cerebrum 8.94 N/A Surgical removal [Dowling] None None None Albendazole Recovered Borni et al [86] Tunisia Case report 1 5 M Headache, vomiting CT, contrast MRI Yes 2 Left occipital 1st: 3.39 2nd: 2.25 Positive Surgical removal None Puncture of Cyst None Albendazole Recovered Kojundzicet al [87] Croatia Case report 1 34 F Headache, vomiting CT, MRI Yes 3 Right temporo-parietal 1st:3.8 2nd:2.9 3rd: N/A Positive Surgical removal None None Osteomyelitis Albendazole Improved Siyadatpanah et al [88] USA Case report 1 39 M Right side paresthesia, imbalance MRI Yes 1 Left fronto-parieto-occipital N/A N/A Surgical removal [Dowling] None None None Albendazole Recovered Akrim et al [89] Morocco Case report 1 22 F Headache, vomiting, blurred vision CT Yes >1 Left parieto-occipital N/A N/A Surgical removal [Arana] None None Neurological deficit Albendazole Improved Zeynal et al [90] Turkey Retrospective cohort 12 50 M Headache, left side hemiparesis CT, MRI Yes 1 Right parietal N/A N/A Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 4 55 M Dysarthria, focal seizure CT, MRI Yes 1 Left temporo-parietal N/A N/A Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 40 M Headache, nausea, vomiting CT, MRI Yes 1 Left parietal N/A N/A Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 4 26 M Headache, left side hemiparesis CT, MRI Yes 1 Left parietal N/A N/A Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 35 F Headache, right side hemiparesis CT, MRI Yes 1 Left thalamus N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 25 M Right side hemiparesis CT, MRI Yes 1 Left thalamus N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 4 64 M Dysphasia CT, MRI Yes 1 Right temporal N/A Positive Surgical removal N/A N/A N/A Albendazole Death 27 F Headache, nausea, vomiting, altered consciousness CT, MRI Yes 1 Left parietal N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 13 M Right side hemiparesis CT, MRI Yes 1 Left parieto-occipital N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 62 M Left side hemiparesis CT, MRI Yes 1 Right fronto-parietal N/A Positive Surgical removal N/A N/A N/A Albendazole Death 49 M Headache CT, MRI Yes 1 Right parieto-occipital N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 52 M Headache CT, MRI Yes 2 Left temporal, right frontal N/A Positive Surgical removal N/A N/A N/A Albendazole Glasgow outcome: 5 Ozdol et al [91] Croatia Case report 1 23 M Nausea, imbalance, headache, urinary and fecal incontinence MRI No 1 Left cerebellum 2.08 Positive Surgical removal None None None Albendazole Recovered Ma et al [92] China Case report 2 50 M Headache, nausea, vomiting Contrast CT, contrast MRI Yes 2 Right frontal, left temporal N/A N/A Surgical removal None None None Albendazole Recovered 42 F Headache, vomiting Contrast CT, contrast MRI Yes 2 Left frontal, left temporal N/A N/A Surgical removal None None None Albendazole Recovered Mokhtari et al [93] Iran Case report 1 60 F Headache, bilateral decreased vision, delusions, cognitive disorders Contrast CT, MRI Yes 2 Left fronto-parietal, right parieto-occipital 1st: 3 2nd: 2.08 N/A Surgical removal None None None Albendazole Recovered Benzagmout et al [94] Morrocco Case report 2 21 F Seizure Contrast CT, contrast MRI Yes 1 Right frontal N/A N/A Surgical removal None None None Antiepileptic Recovered 24 F Headache, vomiting CT No 1 Right frontal 4.47 N/A Surgical removal None None None Albendazole Recovered Ray et al [95] India Case report 1 4 M Headache, nausea, vomiting, altered sensorium, fever CT Yes >1 Left fronto-parietal N/A Negative Surgical removal [ Dowling] N/A N/A Meningitis, subdural effusion, hydrocephalus N/A Recovered Yiş et al [96] Turkey Case report 1 7 M Headache, vomiting, myalgia, abdominal pain MRI Yes 1 Temporo-parieto-occipital 8 N/A Surgical removal [ Dowling] None None None Mebendazole Recovered Per et al [97] Turkey Case series 5 15 M Headache, intellectual impairment, dysphasia CT Yes 4 Left fronto-parietal , left occipital N/A N/A Surgical removal [ Dowling] None None None N/A Recurrence & Death 15 M Headache, faintness, diplopia, vomiting CT, MRI Yes 1 Right temporo-parietal N/A N/A Surgical removal [ Dowling] None None None Albendazole Recovered 4 F Headache, nausea, vomiting, seizure CT Yes 1 Right parietal N/A N/A Surgical removal [ Dowling] None None None Albendazole Recurrence 16 M Vomiting , seizure, headache MRI Yes 1 Right parietal N/A N/A Surgical removal [ Dowling] None None None Albendazole Recovered 11 M Headache, vomiting, strabismus MRI Yes >1 Right occipital,right parietal N/A N/A Surgical removal [ Dowling]/neuronavigation None None None N/A Improved Radmenesh et al [98] Iran Case report 2 7 F Headache,vomiting, right side hemiparesis CT Yes 4 Left frontal N/A Negative Surgical removal None None Hydrocephalus Albendazole Recovered 12 M Headache,vomiting CT Yes 1 Right fronto-temporal N/A Negative Surgical removal None None None Albendazole Recovered Balak et al [99] Turkey Case report 1 16 M Headache, visual disturbance CT, MRI Yes 1 Right parieto-occipital 6 Positive Surgical removal/microsurgery None None None Albendazole Recovered Najjar et al [100] Saudi Arabia Case report 1 11 M Left side hemiparesis CT, contrast MRI Yes 1 Right hemisphere 8 Negative Burr-hole surgical removal None Puncture of Cyst Abscess at surgical site Albendazole Recovered Tatli et al [101] Turkey Case report 3 7 M Headache, left side hypoesthesia CT, MRI Yes 1 Right parietal 7.65 N/A Surgical removal [Dowling] None None None Albendazole Recovered 15 F Headache, vomiting CT Yes 1 Left fronto-parietal 8.48 N/A Surgical removal [Dowling] None Rupture of cyst None Albendazole Recovered 10 F Headache, vomiting, left side weakness CT, MRI Yes 1 Right fronto-temporo-parieto-occipital 10.32 N/A Surgical removal [Dowling] None None None Albendazole N/A Yurt et al [102] Turkey Case report 1 19 F Headache, vomiting, seizure CT, MRI Yes >1 Bilateral hemispheres N/A Negative Multiple surgeries Left side hemiplegia, deterioration None Recurrence of symptoms Albendazole Recurrence Aydin et al[103] Turkey Case report 1 7 M Headache,behavioral disturbance, counting and calculation disorders, mental regression CT Yes 1 Left temporo-parietal 7.48 Positive Surgical removal None None Left hemiparesis Mebendazole Recovered Tuzun et al [104] Turkey Case series 13 9 M Headache, seizure CT, MRI Yes 1 Left parieto-occipital N/A N/A Surgical removal [Dowling] Deterioration None Subdural effusion Albendazole Improved 5 M Right side hemiparesis CT, MRI Yes 1 Left parieto-occipital N/A N/A Surgical removal [Dowling] None None Porencephalic cyst Albendazole Improved 16 F Headache, nausea, vomiting CT, MRI Yes 1 Right parieto-occipital N/A N/A Surgical removal [Dowling] None None None Albendazole Improved 11 F Headache, nausea, vomiting CT, MRI Yes 1 Left temporo-parietal N/A N/A Surgical removal [Dowling] None None Cerebral spinal fluid collection Albendazole Improved 12 M Left side hemiparesis, seizure CT, MRI Yes 1 Right frontal N/A N/A Surgical removal [Dowling] Deterioration None Subdural effusion Albendazole Improved 8 F Headache, loss of consciousness CT, MRI Yes 1 Left fronto-parietal N/A N/A Surgical removal [Dowling] Deterioration None None Albendazole Improved 3 M Right side hemiparesis CT, MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] Deterioration None Subdural effusion Albendazole Improved 17 M Headache, left side hemiparesis CT, MRI Yes 1 Right parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Improved 18 M Headache, right side hemiparesis CT, MRI Yes 1 Left fronto-parietal N/A N/A Surgical removal [Dowling] None None Hemorrhage Albendazole Improved 16 F Right side hemiparesis CT, MRI Yes >1 Left occipital, left parietal N/A N/A Surgical removal [Dowling] None Rupture of cyst None Albendazole Recurrence 11 M Headache CT, MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Improved 9 F Headache, nausea, vomiting CT, MRI Yes 1 Right occipital N/A N/A Surgical removal [Dowling] None None Hemorrhage Albendazole Improved 5 F Headache, right side hemiparesis CT, MRI Yes 1 Left parietal N/A N/A Surgical removal [Dowling] None None None Albendazole Improved Bakaris et al [105] Turkey Case report 1 8 F Right upper paresis, headache CT Yes 1 Left temporo-parieto-occipital 8.14 N/A Surgical removal None None None Albendazole Recovered Guney et al [106] Turkey Case report 1 18 M Headache, neck pain CT Yes 1 Left fronto-parietal N/A Positive Surgical removal None None None N/A N/A Önal et al [107] Turkey Case report 1 7 F Ataxia, apraxia, Headache, tremor CT, MRI Yes 1 Right temporo-parietal 6.21 N/A Surgical removal [Dowling] None None None N/A Recovered Muthusubramanian et al [108] India Case report 1 40 F Headache, right side hemiparesis, double vision, gait abnormality Contrast CT Yes 1 Pons N/A N/A Surgical removal None None None N/A Improved Kabatas et al [109] Turkey Case report 1 26 F Headache, nausea, vomiting, seizure MRI Yes 1 Left frontal 4.13 Positive Surgical removal [Dowling] None None None Albendazole Improved Menkü et al [110] Turkey Case report 1 35 M Seizure CT, MRI No 1 Righ parieto-occipital 4.74 Negative Surgical removal None None None N/A Recovered Anvari et al [111] Iran Case report 1 5 F Headache, nausea, vomiting Contrast CT No 1 Right fronto-parietal N/A N/A Burr-hole surgical removal None None None Albendazole Recovered Karadag˘et al [112] Turkey Case report 1 45 F Seizure, confusion CT Yes 2 Left fronto-parietal, right parietal 5 Negative Surgical removal Deterioration Puncture of the left cyst None Albendazole Recurrence CT; computed tomography, MRI; magnetic resonance imaging, ISHC; Imaging suggested hydatid cyst, N/A; non-available, OP; operative, *Improved = Symptomatic improvement but not complete recovery during the follow-up period. Recovered = Complete recovery/free of symptoms. Table 2. Baseline characteristics of the study and the participants. Variables Frequency/Percentage Country of study Turkey Iran India Morocco Iraq Pakistan Croatia Others 27 (24.1%) 19 (16.7%) 17 (15.2%) 11 (9.8%) 5 (4.6%) 5 (4.6%) 3 (2.7%) 25 (22.3%) Study design Case Report Case Series Retrospective cohort 101 (90.2%) 10 (8.9%) 1 (0.9%) Age, year, mean [SD] 20.44± 16.76 Age group ≤9 10-19 20-29 30-39 40-49 50-59 60-69 70-79 80-89 52 (29.2%) 62 (34.8%) 24 (13.5%) 12 (6.7%) 12 (6.7%) 10 (5.6%) 3 (1.7%) 1 (0.6%) 2 (1.1%) Gender Male Female N/A 107 (60.1%) 68 (38.2%) 3 (1.7%) Residency Rural Urban N/A 71 (39.9%) 8 (4.5%) 99 (55.6%) Previous history of hydatid disease Yes No N/A 13 (7.3%) 161 (90.5%) 4 (2.2%) Type of hydatid disease Cystic Alveolar 158 (88.8%) 20 (11.2%) Presentation Symptomatic Asymptomatic 168 (94.4%) 10 (5.6%) Presenting complaint Headache Vomiting Nausea Seizure Paresis Impaired vision Impaired conscious level Speech abnormalities * Fever Altered sensorium ** Psychological disturbance Other symptoms 112 (62.9%) 77 (43.3%) 35 (19.7%) 54 (30.3%) 51 (28.7%) 23 (13%) 12 (6.7%) 10 (5.6%) 8 (4.5%) 8 (4.5%) 7 (4.0%) 31 (17.4%) Duration of presenting symptoms [mean] 19 weeks Multiple organ involvement Yes No N/A 48 (27%) 128 (71.9%) 2 (1.1%) Site of the cyst/lesion [s] Left-side multi-lobe involvement Right-side multi-lobe involvement Bilateral multi-lobe involvement Frontal lobe Parietal lobe Temporal lobe Occipital lobe Left Hemisphere [unspecified location] Right Hemisphere [unspecified location] Other [Cerebellum, Thalamus, Pons] 50 (28.1%) 47 (26.4%) 11 (6.2%) 17 (9.6%) 33 (18.5%) 5 (2.8%) 4 (2.2%) 2 (1.1%) 2 (1.1%) 7 (4%) Disease status per number of cysts/lesions Primary-solitary Primary-multiple Secondary-solitary Secondary-multiple 118 (66.3%) 27 (15.1%) 23 (13%) 10 (5.6%) Neurological+/-other physical examination Normal Positive findings N/A 30 (16.8%) 92 (51.7%) 56 (31.5%) CT/MRI Findings Suggesting hydatid disease Not suggesting hydatid disease 170 (95.5%) 8 (4.5%) Serology Positive Negative N/A 34 (19.1%) 21 (11.8%) 123 (69.1%) Type of management Conservative Surgical/Open *** Burr-hole 5 (2.8%) 170 (95.5%) 3 (1.7%) Disease outcome Death Survived N/A 6 (3.4%) 139 (78.1%) 33 (18.5%) Recurrence Recurrence alive Recurrence dead 11 (6.2%) 2 (1.1%) * Speech abnormalities: aphasia, apraxia of speech, dysphonia, slurred speech, and others. **Altered sensorium: paresthesia, numbness, and heaviness. *** Surgical removal by (Dowling technique, modified Arana-Inguinz technique, surgical removal under neuronavigation, and microsurgery). Discussion The World Health Organization (WHO) has categorized human echinococcosis under the umbrella of tropical neglected diseases (TNDs) that require control, as the disease remains a significant health issue in endemic regions [1]. Domestic dogs serve as the primary definitive hosts for both species of Echinococcus and pose the highest risk of transmitting cystic and alveolar echinococcosis to humans. Infection in dogs occurs when they consume livestock offal containing hydatid cysts, after which they release parasite eggs in their feces, contaminating soil, water, and grazing fields. Livestock acquire the infection by ingesting these eggs during grazing, while humans are most often infected through eating or drinking contaminated food or water [114,115]. In this systematic review, studies on two genera of clinical interest, Echinococcus granulosus and Echinococcus multilocularis, have been reviewed. Several mechanisms have been proposed for the migration of Echinococcus larvae to the brain. Larvae hatching from ingested eggs in the intestine enter the portal circulation, spreading to different tissues where they develop hydatid disease. Two barriers can protect against CNS involvement: the first is the liver through portal circulation, and the second is the lung, which may act as a secondary filter. The lack of these effective sieves, problems in the immune system, special architecture of brain tissue, disrupted capillaries in the lungs, and structural heart diseases such as patent ductus arteriosus and patent foramen ovale may all provide a gateway to the brain [10,11]. This disease commonly affects supratentorial regions of the brain, specifically within the distribution of the middle cerebral artery, primarily targeting the parietal and frontal lobes [77,78,107]. Generally, BHD is classified as “primary” or “secondary”. The primary disease is rare; it results from direct infestation of the brain without the involvement of other organs. It most often presents as a solitary, spherical, and unilocular cyst surrounded by a broad capsule, which usually contains protoscoleces and renders a fertile lesion. The secondary type is typically characterized by multiple cerebral cysts that result from the rupture of a cyst in other organs. They lack brood capsules and protoscoleces, rendering them infertile. Therefore, the risk of recurrence after their rupture is negligible. However, on rare occasions, multiple primary cysts can occur within the brain parenchyma due to multiple larval intakes in patients with defective immune systems, metastatic deposits from the rupture of a primary cyst in the brain, or the presence of cardiac anomalies. On the other hand, alveolar disease tends to result in multiple intracerebral lesions and might resemble and behave as a malignant lesion [90-93]. Cerebral HD is considered a childhood disease, most commonly (50–75%) seen in children and young adults. Additionally, patients with cerebral HDs may also have concomitant cysts in other organs, although this occurs in less than 20% of patients with intraparenchymal hydatidosis [5,6,105]. In this systematic review, most of the cases (64%) were affected during their first and second decades of life. Multiple cysts or lesions were present in about 21% of the cases. Among these, 15.1% were primary multiple diseases, while only 5.6% of the cases had secondary multiple hydatidosis. Thus, the findings of this review disagree with the assumption that primary multiple BHD is rarer than secondary multiple lesions. Additionally, 48 cases (27%) had concomitant disease in other organs. Signs of raised intracranial pressure (headache, nausea, vomiting) and focal neurological deficits are the most common presentations of the disease. Seizures, visual disturbances, and cranial nerve involvement are also common presenting complaints reported in the literature [103,104]. In this study, headache was the most common presenting symptom (62.9%), followed by vomiting (43.3%), similar to the other reported studies. Seizure, paresis, nausea, and visual disturbance were reported in 30.3%, 28.7%, 19.7%, and 13% of the cases, respectively. The mean duration of symptoms at the time of presentation was 19 weeks. Timely diagnosis of BHDs is crucial because failure to make a prompt diagnosis could result in fatal consequences. Moreover, handling the cystic or mass lesion during surgical intervention is essential for reducing intraoperative complications and preventing disease recurrence. It has been declared that serological testing for the diagnosis of HD is of limited accuracy. Therefore, it is not sufficient on its own to confirm the diagnosis of HD [104]. Imaging modalities are the mainstay of diagnosis in patients with suggestive history and clinical findings, even when serological tests are negative. The disease generally poses common characteristics and pathognomonic features on scanners. Typically, CT and MRI are the primary imaging techniques, which can often be sufficient to achieve a diagnosis. For BHD, the main appearance on CT is a round, intra-parenchymal, usually large cystic lesion with a well-defined border. The cyst fluid is typically isodense or slightly hyperdense compared to cerebrospinal fluid. Calcifications or septations may or may not be present. Calcifications are primarily peri-cystic, giving a 'ground-glass' appearance, suggesting infection or damage before the larva's death. The MRI scans show a thin-walled spherical cyst containing fluid with cerebrospinal fluid characteristics on all sequences. Rim wall contrast enhancement and peripheral edema are much less common in hydatid cysts, and when present, may suggest other radiological differential diagnoses. The presence of multiple small daughter endocysts, characteristic of cystic echinococcosis, is the key distinguishing feature from other cystic lesions in the brain [1-4]. There are a few reports on the CT and MRI appearance of cerebral AE. The lesions may appear as solid, semisolid, or lobulated cystic or mass lesions with definite margins. Calcifications are usually scattered throughout the lesion, unlike in CE, where they are mainly confined to the pericystic region. Predominant features include surrounding edema and various types of contrast enhancement, such as peripheral ring-like, heterogeneous, nodular, and cauliflower-like patterns, indicating an inflammatory reaction around the lesion. Diffusion-weighted MRI is useful in distinguishing lesions from edema. Therefore, the diagnosis should be based on evidence of a primary focus in another location, an appropriate clinical history, the prevalence of the infection in the host's geographic location, and laboratory findings, as a standard practice for diagnosing and differentiating cerebral AE [90-94]. Following laboratory tests and imaging, a histopathological examination confirms the final diagnosis [80,97]. Regarding the findings of this systematic review, a serology test was performed in 30.9% of the studies, and it was positive in 19.1% of the cases. Although this study could not statistically confirm the exact role of serology in detecting BHD, the data suggest that serology alone cannot be relied upon for diagnosing cerebral HD. Additionally, imaging modalities, including both CT and MRI, were indicated for the diagnosis of the disease in 95.5% of cases. The management of BHD typically involves a combination of surgical and adjunctive medical therapies. The treatment plan may vary depending on the size, number, location, and depth of invasion of the lesions into the brain parenchyma. Consequently, the prognosis of the disease can vary based on these factors. The most effective method is surgery. Although different surgical techniques have been investigated, there is consensus that intact cyst removal and total resection of the mass lesion without rupturing it or spilling its contents should be the core of the surgery. This approach is crucial in preventing perioperative complications, recurrence, and progression of the disease. The Dowling-Orlando technique, later modified by Arana-Iniguez and San Julian, is the most widely used surgical method for removing CNS hydatid cysts. This technique involves the formation of a hydrostatic assistant and continuous irrigation with hypertonic saline to dissect the cyst wall from the brain parenchyma, thereby achieving the intact removal of the cyst [26,42,53]. The location of the cyst, its size, adhesion to surrounding structures, multiplicity, and the presence of deep-seated lesions, especially in cases of alveolar E. multilocularis, can make the removal of the cyst intact challenging. The Dowling-Orlando technique may not be feasible in all cases of brain HD. In such situations, alternative methods aimed at minimizing the spillage of the cyst contents can be considered. The PAIR technique, which involves puncture and needle aspiration of the cyst, followed by the injection of a scolicidal solution for 20-30 minutes and cyst re-aspiration, has been reported as a reasonable approach [74,75,111]. Furthermore, the technique of burr-hole opening over the site of the cyst and the introduction of a cannula through the brain to drain the cyst, followed by removal of the cyst wall, has also been reported. However, this method of aspiration is discouraged unless total removal by other techniques is impossible. In patients with brain AE, radical excision should be performed for all accessible lesions. These procedures can be combined with the use of microsurgical and neuronavigation modalities to reduce perioperative complications [56,104]. Intraoperative cyst rupture is a common and serious event. Spillage of the cyst content into the brain tissue may lead to a fatal anaphylactic reaction, which is a chief cause of mortality during surgery. Furthermore, it increases the risk of high recurrence rates of the disease, particularly if the cyst is primary, as it is a fertile lesion [33,35]. The main reported early post-operative complications often arise due to the space left after the excision of large lesions. These may include subdural hematomas, hyperpyrexia, cerebral edema, cortical collapse, or even cardiorespiratory failure. Late post-operative complications such as porencephalic cyst, hydrocephalus, pneumocephalus, hemorrhage, seizures, and focal neurological deficits can occur in the days following surgery. These complications may require conservative management or further intervention [11,20,33]. Although the principal treatment of HD is surgery, pre-and post-operative adjunctive anthelmintic therapy, mainly with albendazole, may be considered. Albendazole can sterilize the cysts, decrease the tension in the cyst wall (thus reducing the risk of spillage during surgery and subsequently the risk of anaphylaxis and recurrence), and is also used for inoperable lesions. The optimal duration of treatment is still unclear, but recommended regimens involve albendazole taken orally at 10–15 mg/kg/day for 3–6 months, followed by a 'rest period' of 15 days after each month. Supportive medications can also be used to manage the presenting symptoms associated with the disease [12,93]. Among the several reviewed studies, a history of traumatic cyst rupture or iatrogenic cyst puncture during surgical procedures played a role in causing the recurrence of the disease [14,76,97]. In the present study, the primary treatment was surgical intervention in most cases (97.2%). The surgical approaches were commonly Dowling-Orlando or modified Arana-Iniguez (95.5%), while three cases (1.7%) underwent burr-hole surgery. In addition, five cases (2.8%) had been managed with conservative treatment only. The recurrence was reported in 13 cases (7.3%). Among them, six cases had intraoperative rupture of the cyst, and two had iatrogenic puncture of the cyst. No alveolar cases showed a recurrence. For this reason, this study recommends surgical intervention over conservative treatment. Follow-up for up to two years is recommended, especially in cases of giant hydatid disease or perioperative complications. In this systematic review, the mean follow-up period was 12 months. It has been reported that the majority of BHD cases can recover and survive with proper management [11,20]. Accordingly, the mortality rate in this study was only 3.4%. The major limitation of this study is the predominantly descriptive nature of the included studies, which may not yield reliable outcomes and can introduce bias. Further research employing rigorous study designs, such as trials comparing different surgical techniques for managing BHD, is recommended, particularly for the alveolar form. Conclusion Imaging modalities, such as CT and MRI, are the primary diagnostic tools for intra-parenchymal BHD, while serological tests alone are not reliable. Surgical intervention remains the definitive treatment for BHD. However, clinical diagnosis and treatment of AE continue to pose significant challenges. Therefore, in endemic regions, early diagnosis and treatment are crucial for improving prognosis. A history of cyst rupture during surgery may increase the risk of recurrence, necessitating extensive follow-up. Declarations Conflicts of interest: The authors have no conflicts of interest to disclose. Ethical approval: Not applicable. Patient consent (participation and publication): Not applicable. Funding: The present study received no financial support. Acknowledgements: None to be declared. Authors' contributions: FHF and ASH were significant contributors to the conception of the study and the literature search for related studies. HOA and ABL involved in the literature review, study design, and manuscript writing. ZOKA, KAA, RJR, AKG, SMA, and ADA were involved in the literature review, the study's design, the critical revision of the manuscript, and data collection. FHF and HOA confirm the authenticity of all the raw data. All authors approved the final version of the manuscript. Use of AI: ChatGPT-4.0 was used to assist in language editing and improving the clarity of the manuscript. All content was reviewed and verified by the authors. Authors are fully responsible for the entire content of their manuscript. Data availability statement: Not applicable.